Strategi Komunikasi Kominfo Pada Program Podcast Di Media Youtube Dalam Menyampaikan Informasi Pada Masyarakat Kota Padang Panjang - Zikra Mutia Fitri; Ria Edlina (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2021)
In presenting information, Kominfo chose social media in disseminating information, one of which was through the official Kominfo Youtube channel called Padang Panjang TV. In its strategy, the Ministry of Communication and Informatics chose Youtube as the medium in providing information because of the Podcast program which is currently a trend among young people. Therefore, this research was conducted to find out how the Communication Strategy of Communication and Informatics in the Podcast Program on Youtube Media in conveying information and its obstacles. This research is a qualitative research using descriptive method, the researcher uses this method because the researcher explores a particular case in greater depth regarding the communication strategy of Kominfo on youtube media in conveying information. Data collection techniques using observation, interviews, and documentation. The main informant in this study is the head of the section for managing information and public communication, someone who is responsible for disseminating information on YouTube media and the supporting informants are the people who are the target recipients of information. In this study, the researcher uses media wealth theory because media wealth theory has four criteria, namely the ability of the media to use multiple media, the speed of feedback, the variety of languages used, and the personal focus of the media. Therefore, from the theory of media wealth, we want to see the communication strategies used in conveying information.